Gestão de patrimônio: reavaliação de ativos no serviço público - Lisboa, Debora Nunes [UNIFESP] (2015)
The advent of convergence of the international accounting standards motivationed changes in current regulations in Brazil; such suitability hit private and public initiatives. The convergence, in order to harmonize the accounting information for the public sector, has brought significant changes that require the need for control and measurement of incident modifications on assets. Since then, standards that were previously optional are now obligatory, such as depreciation and revaluation of public properties. For the revaluation of existing public properties can occur in various government agencies, the Secretaria do Tesouro Nacional - STN, based on Normas Brasileiras de Contabilidade Técnicas Aplicada ao Setor Público - NBC T 16.1, normative issues instructions to guide and determine the application procedures. However, are ample informations that can be followed by several paths, left to the discretion of the agencies to define an appropriate and possible realization methodology. The study arises from the requirements related to the changes originated by the process of convergence to international accounting standards in the public service. In the following chapters will be presented the proposed methodology to meet the asset revaluation account of the accounting devices, medical equipment and appliances, dental and hospital. For this, will be used data of Federal University of São Paulo UNIFESP Campus São José dos Campos.